Prospects for utilizing microbial consortia for lignin conversion - Rodriguez, Alberto; Hirakawa, Matthew P.; Geiselman, Gina M.; Tran-Gyamfi, Mary B.; Light, Yooli K.; George, Anthe; Sale, Kenneth L. (Frontiers in Chemical Engineering, 2023)
Naturally occurring microbial communities are able to decompose lignocellulosic biomass through the concerted production of a myriad of enzymes that degrade its polymeric components and assimilate the resulting breakdown compounds by members of the community. This process includes the conversion of lignin, the most recalcitrant component of lignocellulosic biomass and historically the most difficult to valorize in the context of a biorefinery. Although several fundamental questions on microbial conversion of lignin remain unanswered, it is known that some fungi and bacteria produce enzymes to break, internalize, and assimilate lignin-derived molecules. The interest in developing efficient biological lignin conversion approaches has led to a better understanding of the types of enzymes and organisms that can act on different types of lignin structures, the depolymerized compounds that can be released, and the products that can be generated through microbial biosynthetic pathways. It has become clear that the discovery and implementation of native or engineered microbial consortia could be a powerful tool to facilitate conversion and valorization of this underutilized polymer. Here we review recent approaches that employ isolated or synthetic microbial communities for lignin conversion to bioproducts, including the development of methods for tracking and predicting the behavior of these consortia, the most significant challenges that have been identified, and the possibilities that remain to be explored in this field.